Esophageal foreign bodies: our experience - Muzaffar, Rahil; Malik, Altaf; Khurshid, Sumat Ul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The objective of this prospective study was to report our experience of presentation and management of esophageal foreign bodies at GMC Doda. Methods: This prospective study was conducted in the department of ENT at GMC Doda from January 2019 to October 2022. During this time period 43 patients of foreign body ingestion were admitted in the department of ENT. Of the 43 patients 27 were male and 16 were female patients. 34 were children and 9 patients were adults. After doing through examination, plain radiograph was done on admission in all patients. Age appropiate rigid endoscope was used for foreign body extraction under general anaesthesia. Results: In children the coin was the most common type of foreign body (28 patients, 82.3%), with about 39% managed conservatively after overnight observation,as the coin passed on spontaneously. In adults chicken bone was the most common type of foreign body (5 patients, 55%). Upper esophagus (cricopharynx) was the most common site of foreign body impaction in both adults and pediatric patients. Rigid endoscope was used in all patients requiring intervention. Conclusions: Our study suggests that pediatric patients have higher incidence of foreign body ingestion as compared to adults. Management depends on the type of foreign body ingested as many can pass on spontaneously without requiring any invasive intervention. Also the rigid endoscope is a safe, effective and cheaper instrument that is used for removal of foreign body from esophagus.